2008
DOI: 10.1111/j.1423-0410.2008.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of clot formation in fresh‐frozen plasma

Abstract: We conclude that levels of FVIII do not predict the haemostatic potential of FFP and that there may be a role for alternative technologies in monitoring the quality of FFP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…There are several studies documenting clinical relevance of MPs in supporting coagulation [32-38]. We and others have previously shown that PMPs, generated during extended blood storage, contribute to functional hemostasis in stored plasma and correlate with enhanced thrombin generation [12, 39]. However, since MPs are heterogenous and contain many proteins with opposing activities (pro- and anti-coagulants, proteases and their inhibitors), more detailed studies are needed to elucidate their specific roles in severe trauma with coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies documenting clinical relevance of MPs in supporting coagulation [32-38]. We and others have previously shown that PMPs, generated during extended blood storage, contribute to functional hemostasis in stored plasma and correlate with enhanced thrombin generation [12, 39]. However, since MPs are heterogenous and contain many proteins with opposing activities (pro- and anti-coagulants, proteases and their inhibitors), more detailed studies are needed to elucidate their specific roles in severe trauma with coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…While classical quality parameters like FVIII are based on the determination of a single coagulation factor only, thrombin generation assays might be a valuable indicator for the overall hemostatic potential of FFP. However, to date there is only very limited data on thrombin generation in FFP [13,14]. Lawrie et al [13] assessed thrombin generation in FFP prepared under different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date there is only very limited data on thrombin generation in FFP [13,14]. Lawrie et al [13] assessed thrombin generation in FFP prepared under different conditions. Also Pock et al [14] determined thrombin generation parameters in FFP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, miRNA-21 has been found to be overexpressed in diffuse large B cell lymphoma and is validated as an independent risk factor in prognosis [1012]. miRNA-21 is also a diagnostic biomarker in primary diffuse large B cell lymphoma of the central nervous system [13].…”
Section: Introductionmentioning
confidence: 99%